Chronic kidney disease and periodontal disease. Case report - Nunes, Camilla Magnoni Moretto [UNESP]; Ferreira, Camila Lopes [UNESP]; Bernardo, Daniella Vicensotto [UNESP]; De Marco, Andréa Carvalho [UNESP]; Santamaria, Mauro Pedrine [UNESP]; Jardini, Maria Aparecida Neves [UNESP] (Editora Cubo, 2018)
Chronic renal disease promotes a decrease on kidneys filterability and nitrogen products accumulation on blood, electrolyte and system endocrine functions imbalance. Among the many clinical manifestations of chronic renal failure (CRF) in the oral cavity, there are: dry mouth, uremic stomatitis, radiographic changes in maxillary and jaw bones and accumulation of calculus on the teeth that increases levels of periodonto pathogenic microorganisms able to lead a periodontal tissue destruction and also have the potential to act from a distance on other organs, e.g. the kidneys. Thus,it becomes evident that a periodontal treatment of patients suffering from chronic renal failure is crucial for maintaining their general health conditions and a subsequent successful organ transplant.Thus, the objectives of this case report were to highlight how important the periodontal treatment is for chronic renal failure patients and to demonstrate improvements in their clinical condition through the treatment plan proposed herein. A patient with 43 years old carrier generalized moderate chronic periodontitis and CRF was submitted to scaling and root planning sessions, and later surgical access for scaling where the basic treatment not resulted in a resolution of the inflammatory periodontal process. The results obtained from a well-developed periodontal treatment and an effective cooperation of patient showed satisfactory results with periodontal disease process resolution or stabilization.Thus, periodontal treatment and patient compliance were crucial for the improvement of periodontal clinical conditions enabling a future successful renal transplantation.
Doença renal crônica e tratamento periodontal. Relato de caso
Keywords: Dental care; Periodontal diseases; Renal insufficiency